Supportive relationships in childhood: Does it have a long Reach into health and depression outcomes for immigrants from Latin America? - Andrea G. Perez Portillo; Jerald R. Herting; Jane J. Lee; Bonnie Duran (Elsevier, 2023)
This study examines how social support during childhood and adolescence is associated with self-rated good health and the incidence of depression among Latin American immigrants in the U.S. We focus on those who immigrated under age 18 (childhood arrivals) to understand the interplay between early social support and adult health outcomes. Data are from the 2012-2013 iteration of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC-III), which included a sample of 3441 immigrant respondents born in Latin America. Multivariable binomial logistic regression analyses indicated that childhood and interpersonal support in adulthood were negatively associated with lifetime major depressive disorder (LMDD) episodes. These associations differed between childhood arrival and adult arrival immigration samples. Findings from this study highlight the role that social support in critical developmental periods has on immigrant health and depression outcomes. Continued and more nuanced investigations are warranted to examine social resources across lifespans and their roles in mitigating adverse health outcomes among immigrants from Latin America.